(untitled) (World Economics and Finance Bulletin, 2026)
The article examines the theoretical foundations and current challenges of improving strategic management and international cooperation in the field of digital finance. It clarifies the concepts of “digital finance” and “strategic management in a digital environment”, and analyzes key forms of international partnership and competency requirements for specialists. The paper substantiates key improvement areas, including the introduction of competency-based models, alignment of university strategies with national digitalization programs, the expansion of international educational tracks, and the establishment of digital finance competence centers